Enhanced Transdermal Delivery of Epidermal Growth Factor Facilitated by Dual Peptide Chaperone Motifs - Jin, Pei-pei; Li, Fen-fen; Ruan, Ren-quan; Zhang, Li; Man, Na; Hu, Yi; Zhou, Wei; Wen, Long-ping (Protein and Peptide Letters, 2014)
TD1, a peptide chaperone consisting of the sequence ACSSSPHKHCG, has been shown to facilitate transdermal delivery for protein molecules via either co-administration or the fusion approach. We previously reported that a single TD1 motif, fused to the N-terminus of human epidermal growth factor (hEGF) can significantly enhance the transdermal efficiency of the recombinant EGF protein. In an effort to further increase the transdermal efficiency, we have created EGF fusion proteins harboring dual TD1 motifs: TD1-hEGF-TD1, containing one TD1 motif at both the N- and the Cterminus, and TD1-TD1-hEGF, containing two tandem TD1 motifs at the N-terminus. Both TD1-hEGF-TD1 and TD1- TD1-hEGF proteins, expressed in Escherichia coli and purified to apparent homogeneity, exhibited biological activity similar to unmodified hEGF, as revealed by their relative abilities to stimulate fibroblast growth, promote fibroblast migration, and activate the MAP kinase signaling cascade. On the other hand, both TD1-hEGF-TD1 and TD1-TD1-hEGF proteins exhibited a transdermal efficiency enhancement. The improvement was >5-fold compared to unmodified hEGF and 3-fold over the hEGF fusion protein with only one TD1 motif attached. These findings provided proof-of-concept for improving transdermal delivery of protein actives through rational protein design.
Keywords: human epidermal growth factor